OPTIMIZATION OF MICROWAVE ASSISTED EXTRACTION PROCESS ON OLEORESIN OF KUWENI MANGO PEELS EXTRACTS USING SURFACE RESPONSE METHODOLOGY - Abdurrahman Hanif; Asri Widyasanti; Selly Harnesa Putri (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Mango peel is a byproduct that is wasted when processing the fruit into certain products. One mango peel utilization is by extracting the oleoresin content in it. Oleoresin is a spice extractive that contains the main components of flavoring in the form of volatile and non-volatile substances. The research objective was to determine the optimum microwave-assisted extraction (MAE) process condition to produce oleoresin yield of the kuweni mango peel using a combination of two variables: the volume of solvent and length of extraction. The optimization method used was the response surface method (RSM) application. The extraction was carried out in two solvents namely n-hexane and 96% food-grade ethanol. The parameters measured in this study were the yield, residual solvent content, and specific gravity. The results showed that the optimum solution for the extraction process using n-hexane solvent had a combination of 7 minutes extraction time and 200 ml of solvent with the mathematical equation Y = 0.04A + 0.69B - 3.09. The optimum solution for the extraction process using ethanol solvent is in a combination of 3 minutes extraction time and 200 ml of solvent with the mathematical equation Y = 0.07A - 0.46B + 3.14.